Sp1‐mediated epigenetic dysregulation dictates HDAC inhibitor susceptibility of HER2‐overexpressing breast cancer. Issue 12 (4th June 2019) - Li, Guoyin; Xie, Qiaosheng; Yang, Zhiwei; Wang, Lei; Zhang, Xiang; Zuo, Baile; Zhang, Shengli; Yang, Angang; Jia, Lintao
Abstract : Human epidermal growth factor receptor 2 (HER2/erbB2) is a key driver and therapeutic target for breast cancer. The treatment of HER2‐positive breast cancer remains a clinical challenge largely due to the limited understanding of HER2‐driving oncogenic signaling and the frequent resistance to simply HER2‐targeted therapy. Here, we show that the histone deacetylase inhibitor, trichostatin A (TSA), suppresses HER2‐overexpressing breast cancer via upregulation of miR‐146a and the resultant repression of its oncogenic targets, interleukin‐1 receptor‐associated kinase 1 and the chemokine receptor CXCR4. Mechanistically, histone H3K56 acetylation and deacetylation on the MIR146A promoter are catalyzed respectively by the acetyltransferase p300 and histone deacetylase 1 (HDAC1), both of which are recruited to the genomic loci by the transcription factor specificity protein 1 (Sp1). HER2 signaling phosphorylates Sp1 and induces its predominant association with HDAC1, but not p300, leading to histone hypoacetylation and silencing of MIR146A . In addition, the death receptor Fas is similarly downregulated by the aforementioned epigenetic paradigm, indicating its wide involvement in impairing tumor suppressor gene expression. Consequently, TSA synergizes with lapatinib, a tyrosine kinase inhibitor of HER2, to suppress breast cancer in vitro and in rodent models. These findings demonstrate a novel mechanism of HER2‐driven carcinogenesis and suggest the applicability of combined HER2 and HDAC targeting in breast cancer therapy. Abstract : What's new? Signaling through the human epidermal growth factor receptor 2 (HER2) is associated with approximately 20% of breast cancers but the efficacy of anti‐HER2 therapies is severely compromised by drug resistance. Here, the authors uncovered potential benefits of combining anti‐HER2 treatments with inhibitors of histone deacetylases (HDACs). They found HER2 signaling silenced tumor suppressor gene expression by impairing the homeostasis of histone acetylation and manipulating the transcription factor Sp1. These findings offer a new explanation of HER2‐driven carcinogenesis and point to potential benefits of combining HER2‐targeting therapies with HDAC inhibitors.